The Pedagogical Implication of Maybrat Oral Literature (Elements and Value of Character Education) - Sherly Gaspersz; Lulu Jola Uktolseja (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
This research aimed to know the elements in the folklore of Maybrat Regency and value of character education contained in the folklore of Maybrat Regency. The data obtained in this study were three stories from Maybrat Regency which were obtained through the results of interviews with informants who came and were in Maybrat Regency. The research method used is descriptive research method with procedures: conducted interviews, record the interview process, rewrite the results of interviews in this case folklore, analyzed elements in folklore, and analyzing the value of character education in folklore. The results in this research include three stories of Maybrat Regency entitled: (1) The origin of Arus Village, (2) The Origin of Way Clan, and (3) the Origin of Howay Clan. Here the result of analyze elements: (1) the theme of love and hard work, (2) the location of the story in the Maybrat Regency, (3) the characters that appear in family life (husband, wife, siblings, and a group of village people) their life character respects one another, (4) contains a degeneration plot, and (5) contains a positive message to work hard and maintain harmony in life. Furthermore, the value of character education is also contained in this story, namely: discipline, hard work, independence, caring for the environment, responsibility, tolerance and caring for others.